A Mutant Isoform of ObgE Causes Cell Death by Interfering with Cell Division - Dewachter, Liselot; Verstraeten, Natalie; Jennes, Michiel; Verbeelen, Tom; Biboy, Jacob; Monteyne, Daniel; Pérez-Morga, David; Verstrepen, Kevin J.; Vollmer, Waldemar; Fauvart, Maarten; Michiels, Jan (Frontiers in Microbiology, 2017)
Cell division is a vital part of the cell cycle that is fundamental to all life. Despite decades of intense investigation, this process is still incompletely understood. Previously, the essential GTPase ObgE, which plays a role in a myriad of basic cellular processes (such as initiation of DNA replication, chromosome segregation and ribosome assembly), was proposed to act as a cell cycle checkpoint in Escherichia coli by licensing chromosome segregation. We here describe the effect of a mutant isoform of ObgE (ObgE*) that causes cell death by irreversible arrest of the cell cycle at the stage of cell division. Notably, chromosome segregation is allowed to proceed normally in the presence of ObgE*, after which cell division is blocked. Under conditions of rapid growth, ongoing cell cycles are completed before cell cycle arrest by ObgE* becomes effective. However, cell division defects caused by ObgE* then elicit lysis through formation of membrane blebs at aberrant division sites. Based on our results, and because ObgE was previously implicated in cell cycle regulation, we hypothesize that the mutation in ObgE* disrupts the normal role of ObgE in cell division. We discuss how ObgE* could reveal more about the intricate role of wild-type ObgE in division and cell cycle control. Moreover, since Obg is widely conserved and essential for viability, also in eukaryotes, our findings might be applicable to other organisms as well.